Benefits outweigh the risks: a consensus statement on the risks of physical activity for people living with long-term conditions. Issue 8 (14th October 2021) - Reid, Hamish; Ridout, Ashley Jane; Tomaz, Simone Annabella; Kelly, Paul; Jones, Natasha
Abstract : Introduction: The benefits of physical activity for people living with long-term conditions (LTCs) are well established. However, the risks of physical activity are less well documented. The fear of exacerbating symptoms and causing adverse events is a persuasive barrier to physical activity in this population. This work aimed to agree clear statements for use by healthcare professionals about medical risks of physical activity for people living with LTCs through expert consensus. These statements addressed the following questions: (1) Is increasing physical activity safe for people living with one or more LTC? (2) Are the symptoms and clinical syndromes associated with common LTCs aggravated in the short or long term by increasing physical activity levels? (3) What specific risks should healthcare professionals consider when advising symptomatic people with one or more LTCs to increase their physical activity levels? Methods: Statements were developed in a multistage process, guided by the Appraisal of Guidelines for Research and Evaluation tool. A patient and clinician involvement process, a rapid literature review and a steering group workshop informed the development of draft symptom and syndrome-based statements. We then tested and refined the draft statements and supporting evidence using a three-stage modified online Delphi study, incorporating a multidisciplinary expert panel with a broad range of clinical specialties. Results: Twenty-eight experts completed the Delphi process. All statements achieved consensus with a final agreement between 88.5%–96.5%. Five 'impact statements' conclude that (1) for people living with LTCs, the benefits of physical activity far outweigh the risks, (2) despite the risks being very low, perceived risk is high, (3) person-centred conversations are essential for addressing perceived risk, (4) everybody has their own starting point and (5) people should stop and seek medical attention if they experience a dramatic increase in symptoms. In addition, eight symptom/syndrome-based statements discuss specific risks for musculoskeletal pain, fatigue, shortness of breath, cardiac chest pain, palpitations, dysglycaemia, cognitive impairment and falls and frailty. Conclusion: Clear, consistent messaging on risk across healthcare will improve people living with LTCs confidence to be physically active. Addressing the fear of adverse events on an individual level will help healthcare professionals affect meaningful behavioural change in day-to-day practice. Evidence does not support routine preparticipation medical clearance for people with stable LTCs if they build up gradually from their current level. The need for medical guidance, as opposed to clearance, should be determined by individuals with specific concerns about active symptoms. As part of a system-wide approach, consistent messaging from healthcare professionals around risk will also help reduce cross-sector barriers to engagement for this population.